Humidity resistant fabrication of CH3NH3PbI3 perovskite solar cells and modules - Trystan Watson (Nano Energy, 2017)
A humidity resistant and versatile fabrication method for the production of very high quality, organic-inorganic perovskite films, solar cells and solar modules is presented. By using ethyl acetate as an anti-solvent during deposition, perovskite solar cells with power conversion efficiencies (PCEs) up to 15% were fabricated in a 75% relative humidity (RH) environment. Ethyl acetate acts as a moisture absorber during spin-coating, protecting sensitive perovskite intermediate phases from airborne water during film formation and annealing. We have demonstrated the manufacture of 50 mm x 50 mm series interconnected modules with PCEs in excess of 10% for 13.5 cm2 devices processed in air at 75%RH and 11.8% at 50%RH. To the best of our knowledge, these results represent the highest efficiency for perovskite solar modules processed under high humidity ambient conditions. This new deposition protocol allows for low-cost, efficient and consistent device fabrication in humid climates and uncontrolled laboratories.